Higher anterior knee laxity influences the landing biomechanics displayed by pubescent girls - Wild, Catherine; Munro, B.; Steele, J. (Routledge, 2017)
© 2016 Informa UK Limited, trading as Taylor & Francis Group.Despite an increase in anterior knee laxity (AKL) during the adolescent growth spurt in girls, it is unknown whether landing biomechanics are affected by this change. This study investigated whether pubescent girls with higher AKL displayed differences in their lower limb strength or landing biomechanics when performing a horizontal leap movement compared to girls with lower AKL. Forty-six pubescent girls (10–13 years) were tested at the time of their peak height velocity (PHV). Passive AKL was quantified and used to classify participants into higher (HAKL; peak displacement > 4 mm) and lower (LAKL; peak displacement < 3 mm) AKL groups (n = 15/group). Three-dimensional kinematics, ground reaction forces (GRF) and muscle activation patterns were assessed during a horizontal leap landing. HAKL participants displayed significantly (P < 0.05) reduced hip abduction, increased hip abduction moments, as well as earlier hamstring muscle and later tibialis anterior activation compared to LAKL participants. Girls with HAKL displayed compensatory landing biomechanics, which are suggested to assist the functional stability of their knees during this dynamic task. Further research is warranted, however, to confirm or refute this notion.